High-thermal-conductivity and high-modulus silicon carbide ceramic and preparation method thereof
By using technical means such as particle size grading, carbon enlargement impregnation and liquid silicon permeation in the preparation process of silicon carbide ceramics, the problems of low thermal conductivity and elastic modulus of existing silicon carbide ceramics are solved, and silicon carbide ceramics with high thermal conductivity and high elastic modulus are achieved.
Patent Information
- Application Number
- CN202510046969.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-15
AI Technical Summary
The existing reactive sintered silicon carbide ceramics have problems such as more free silicon, low elastic modulus and low thermal conductivity, which is difficult to meet the application requirements of high thermal conductivity and high modulus.
By mixing the silicon carbide raw material powder with solvent and binder, heating curing, carbon enhancing impregnation and liquid silicon penetration treatment after molding, the density and performance of the ceramic are improved.
Silicon carbide ceramics with high thermal conductivity greater than 220W/(m·K) and high elastic modulus greater than 350GPa are achieved, meeting the needs of high performance applications.
Smart Images

Figure CN119822840A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silicon carbide ceramic preparation, and specifically relates to a high thermal conductivity, high modulus silicon carbide ceramic and a preparation method thereof. Background Art
[0002] At present, advanced ceramics that are resistant to high temperatures, wear and corrosion have gradually become an important component of new materials and a key material for the development of many high-tech fields. Among them, silicon carbide ceramic materials are widely used in semiconductor manufacturing, new energy photovoltaics, chemical environmental protection, biomedicine, aerospace, automobile manufacturing and other fields due to their good mechanical properties, high thermal conductivity, low thermal expansion coefficient and excellent chemical stability. In some special applications, such as heat exchanger components, thermal storage combustion and electronic device packaging substrates, more stringent thermodynamic performance requirements are put forward for silicon carbide ceramics.
[0003] At present, the commonly used sintering methods of silicon carbide ceramics mainly include pressureless sintering, hot pressing sintering, spark plasma sintering and reaction sintering. Among them, reaction sintering is widely used in silicon carbide ceramics due to its advantages such as low sintering temperature, near net size forming and short production cycle, especially in combination with additive manufacturing methods to prepare silicon carbide ceramics, which has obvious advantages.
[0004] However, current reaction-sintered silicon carbide generally has problems such as high free silicon content, low elastic modulus, and low thermal conductivity, making it difficult to meet the growing application requirements for low deformation and high stability of silicon carbide ceramics. Summary of the invention
[0005] In view of the problems of high residual silicon content, low thermal conductivity and elastic modulus of the above-mentioned silicon carbide ceramics, the present invention provides a high thermal conductivity, high modulus silicon carbide ceramic and a preparation method thereof.
[0006] In a first aspect, the present invention provides a method for preparing high thermal conductivity and high modulus silicon carbide ceramics, the preparation method comprising the following steps: (1) mixing silicon carbide raw material powder and a solvent for a first time, then adding a binder thereto and mixing for a second time to obtain a silicon carbide raw material mixed slurry; (2) forming the silicon carbide raw material mixed slurry into a green body and performing a heating and curing treatment, and then debonding to obtain a silicon carbide ceramic body; (3) performing a carbon-enhanced impregnation treatment on the silicon carbide ceramic body and performing a debonding treatment to obtain a carbon-enhanced impregnated silicon carbide ceramic body; (4) The carbon-impregnated silicon carbide ceramic body is subjected to liquid silicon infiltration treatment to obtain the high thermal conductivity and high modulus silicon carbide ceramic.
[0007] Preferably, in step (1), the silicon carbide raw material powder includes 2 to 4 silicon carbide raw material powders of different particle size ranges; preferably, the silicon carbide raw material powder includes silicon carbide raw material powders of two particle size ranges, namely, large-particle-size silicon carbide raw material powder and small-particle-size silicon carbide raw material powder; More preferably, the median particle size of the large-particle silicon carbide raw material powder is 100-500 μm, the median particle size of the small-particle silicon carbide raw material powder is 1-100 μm, and the mass ratio of the large-particle silicon carbide raw material powder to the small-particle silicon carbide raw material powder is 6-8:2-4.
[0008] Preferably, in step (1), the solvent comprises at least one of dilute sulfuric acid, hydrochloric acid, phosphoric acid, boric acid, oxalic acid, maleic anhydride, citric acid, malic acid, polyaluminum phosphate, benzenesulfonic acid or phenolsulfonic acid, preferably benzenesulfonic acid or phenolsulfonic acid, more preferably p-toluenesulfonic acid.
[0009] Preferably, in step (1), the binder includes at least one of polyvinyl alcohol, polyvinyl butyral, polymethyl methacrylate, polyvinyl pyrrolidone, water glass, silica sol, epoxy resin, furan resin, and phenolic resin.
[0010] Preferably, in step (1), based on the total mass of the silicon carbide raw material powder, solvent and binder as 100%, the mass of the silicon carbide raw material powder accounts for 85-97wt%, the mass of the solvent accounts for 1-5wt%, and the mass of the binder accounts for 2-10wt%.
[0011] Preferably, in step (2), the temperature of the heating and curing treatment is 120-180° C., preferably 170° C.; and the insulation time is 2-4 hours, preferably 3 hours.
[0012] Preferably, in step (3), the process of the carburizing impregnation treatment comprises: vacuum impregnating the silicon carbide ceramic body in a carburizing impregnation solution, then curing it, and then continuing to vacuum impregnate it in a phenolic resin solution and curing it again.
[0013] Preferably, the raw material composition of the carbon-increasing impregnation liquid includes: 50-80wt% phenolic resin solution, 5-30wt% SiC ultrafine powder, 5-30wt% nano carbon black, and 1-5wt% dispersant; Preferably, the phenolic resin solution is a mixed solution of phenolic resin and anhydrous ethanol, the content of anhydrous ethanol is 30-70wt%, the SiC ultrafine powder is β-SiC ultrafine powder with a particle size of 50-800nm, the particle size of nano carbon black is 1-100nm, and the dispersant is castor oil phosphate or castor oil.
[0014] Preferably, in step (4), the temperature of the liquid silicon infiltration treatment is 1550-1650° C., preferably 1600° C., and the insulation time is 30-90 min, preferably 60 min.
[0015] In a second aspect, the present invention provides a high thermal conductivity, high modulus silicon carbide ceramic obtained according to the above preparation method, wherein the high thermal conductivity, high modulus silicon carbide ceramic has a thermal conductivity greater than 220 W / (m·K) and an elastic modulus greater than 350 GPa.
[0016] Beneficial Effects (1) The present invention combines two silicon carbide powders of different particle sizes, wherein large silicon carbide particles form the main heat conduction channel, and small silicon carbide particles fill the gaps between large silicon carbide particles, so that the silicon carbides are connected to each other, ensuring the connectivity of the heat conduction channel, thereby improving the thermal conductivity of the silicon carbide ceramic; (2) The present invention improves the density of silicon carbide ceramics and reduces the content of residual silicon by two methods: first, by grading the particle size of silicon carbide powder, the packing density of the powder is increased, and the silicon carbide content in the green body is increased; second, by preparing a vacuum impregnation solution with a high carbon content and then using a phenolic resin solution for a second impregnation without debonding, the high carbon content impregnation solution of the first impregnation can fill most of the relatively large pores, and the phenolic resin solution of the second impregnation can fill the remaining small pores. After debonding and cracking, a large amount of carbon is generated, which greatly increases the carbon density of the green body, thereby increasing the density of silicon carbide after siliconization, reducing the content of residual silicon, and improving the thermal conductivity and elastic modulus of silicon carbide ceramics. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a SEM image of the surface morphology of the high thermal conductivity and high modulus silicon carbide ceramic prepared in Example 1; Figure 2 The surface morphology SEM image of the silicon carbide ceramic prepared in Comparative Example 1; Figure 3 This is the SEM image of the surface morphology of the silicon carbide ceramic prepared in Comparative Example 2. DETAILED DESCRIPTION
[0018] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0019] The following is an exemplary description of the preparation method of the high thermal conductivity and high modulus silicon carbide ceramic provided by the present invention. The preparation method may include the following steps: (1) mixing silicon carbide raw material powder and a solvent for a first time, then adding a binder thereto and mixing for a second time to obtain a silicon carbide raw material mixed slurry; (2) forming the silicon carbide raw material mixed slurry into a green body and performing a heating and curing treatment, and then debonding to obtain a silicon carbide ceramic body; (3) performing a carbon-enhanced impregnation treatment on the silicon carbide ceramic body and performing a debonding treatment to obtain a carbon-enhanced impregnated silicon carbide ceramic body; (4) The carbon-impregnated silicon carbide ceramic body is subjected to liquid silicon infiltration treatment to obtain the high thermal conductivity and high modulus silicon carbide ceramic.
[0020] In some embodiments, in step (1), the silicon carbide raw material powder may include 2 to 4 silicon carbide raw material powders with different particle size ranges; preferably, the silicon carbide raw material powder includes silicon carbide raw material powders with two particle size ranges, namely, large particle size silicon carbide raw material powder and small particle size silicon carbide raw material powder.
[0021] The median particle size of the large-particle silicon carbide raw material powder can be 100-500 μm, preferably 100-200 μm. The large particle size of this part of silicon carbide powder can be used to form the main ceramic frame and a good heat transfer channel, and can maintain good mechanical properties.
[0022] The median particle size of the small-size silicon carbide raw material powder can be 1-100 μm, preferably 1-50 μm, and more preferably 20-50 μm. This part of the silicon carbide powder has a smaller particle size and can be used to fill the gaps between the large-size silicon carbide powders, thereby reducing the residual silicon content, increasing the density, and ensuring the continuity of the heat transfer channel.
[0023] The mass ratio of the large-size silicon carbide raw material powder to the small-size silicon carbide raw material powder can be 6 to 8: 2 to 4, preferably 7 to 3. If the large-size silicon carbide powder accounts for too large a proportion, there will be more gaps between the powders, and the density of the ceramic will be reduced; if the large-size silicon carbide powder accounts for too small a proportion, it will be difficult to build a good heat transfer channel, and the thermal conductivity of the ceramic will decrease.
[0024] In some embodiments, in step (1), the solvent may include at least one of dilute sulfuric acid, hydrochloric acid, phosphoric acid, boric acid, oxalic acid, maleic anhydride, citric acid, malic acid, polyaluminum phosphate, benzenesulfonic acid or phenolsulfonic acid, preferably benzenesulfonic acid or phenolsulfonic acid, and more preferably p-toluenesulfonic acid.
[0025] The solvent used in the present invention can help the subsequently added binder to cure quickly and improve the curing strength, thereby improving the green body strength of the silicon carbide ceramic. In addition, this type of solvent can easily remove organic matter at high temperature and generate a large amount of porous carbon, which further reacts with silicon to generate silicon carbide.
[0026] In some embodiments, in step (1), the first mixing method can be planetary ball milling or horizontal drum ball milling, the ball milling medium can be SiC ball milling beads, the ball milling speed can be 100 to 400 r / min, and the ball milling time can be 1 to 5 h.
[0027] In some embodiments, in step (1), the binder may include at least one of polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polymethyl methacrylate (PMMA), polyvinyl pyrrolidone (PVP), water glass, silica sol, epoxy resin, furan resin, and phenolic resin. Such binders have high bonding strength and can react with solvents to rapidly solidify, thereby improving the strength of the ceramic blank. Preferably, epoxy resin, furan resin, and phenolic resin are easily pyrolyzed and removed at high temperatures, and the pyrolysis products are porous carbon.
[0028] In some embodiments, in step (1), the second mixing method can be horizontal drum ball milling or sand mixer mixing, and the mixing time can be 1 to 10 minutes, preferably 1 to 5 minutes. Since the silicon carbide raw material powder and the solvent are mixed for the first time, the solvent is evenly wrapped on the surface of the powder, so it can be quickly solidified after the addition of the binder, and a silicon carbide ceramic blank with high strength is obtained after compression molding. In addition, the mixing time after adding the binder should not be too long to prevent the binder from over-curing and hindering the subsequent compression molding process.
[0029] In some embodiments, in step (1), taking the total mass of the silicon carbide raw material mixed slurry (silicon carbide raw material powder, solvent, binder) as 100%, the mass proportion of the silicon carbide raw material powder can be 85-97wt%, the mass proportion of the solvent can be 1-5wt%, and the mass proportion of the binder can be 2-10wt%. Under this mass proportion, the ceramic is well formed and the green body strength is high. If the mass proportion of the solvent and the binder is too large, the curing process will be too rapid, and the curing will be completed during the mixing process, and the next step of compression molding cannot be carried out. In addition, it will also lead to an increase in the organic content, and the strength of the ceramic green body after debonding will be too low; if the mass proportion of the solvent and the binder is too small, the bonding force will be reduced, and the green body strength after molding will be low, making it difficult to form.
[0030] In some embodiments, in step (2), the molding method can be compression molding; wherein the compression molding pressure can be 20 to 40 MPa, preferably 30 MPa, and the holding time can be 1 to 3 minutes, preferably 2 minutes.
[0031] In some embodiments, in step (2), the heat curing treatment can be carried out in a vacuum oven, an electric blast drying oven or a hot air circulation oven; the temperature of the heat curing treatment can be 120 to 180°C, preferably 170°C; the heat preservation time can be 2 to 4 hours, preferably 3 hours. The heat curing treatment can further promote the curing reaction between the binder and the solvent, improve the bonding strength of the binder, and further improve the strength of the ceramic blank after compression molding.
[0032] In some embodiments, in steps (2) and (3), the debonding can be performed in a vacuum high-temperature furnace, and the atmosphere can be vacuum or inert gas, preferably vacuum atmosphere; the debonding temperature can be 800-1000°C, preferably 900°C; the holding time can be 30-90 minutes, preferably 30 minutes. Under this debonding system, organic matter can be completely cracked and removed, and the cracking product is porous carbon, which can react to form silicon carbide in the subsequent liquid silicon infiltration treatment, thereby improving the density and performance of the ceramic.
[0033] In some embodiments, in step (3), the process of the carbon-increasing impregnation treatment may include: vacuum impregnating the silicon carbide ceramic body in a carbon-increasing impregnation solution, then curing, and then continuing to vacuum impregnate in a phenolic resin solution and curing again. The carbon-increasing impregnation treatment method provided by the present invention can effectively increase the SiC and C content in the green body, and infiltrate them into the silicon carbide body through vacuum pressure, thereby increasing the final silicon carbide ceramic density.
[0034] Wherein, the raw material composition of the carbon-increasing impregnation liquid may include: 50-80wt% of phenolic resin solution, 5-30wt% of SiC ultrafine powder, 5-30wt% of nano carbon black, and 1-5wt% of dispersant; preferably, the phenolic resin solution may be a mixed solution of phenolic resin and anhydrous ethanol, the content of anhydrous ethanol may be 30-70wt% (such as 50wt%), the SiC ultrafine powder may be β-SiC ultrafine powder with a particle size of 50-800nm, the particle size of nano carbon black may be 1-100nm, and the dispersant may be castor oil phosphate or castor oil. Wherein, the phenolic resin solution is used as a basic solution, and the viscosity of the carbon-increasing impregnation liquid can be adjusted by adjusting the content of anhydrous ethanol to ensure that the carbon-increasing impregnation liquid can be vacuum impregnated into the ceramic body. In addition, the phenolic resin can be thermally cured after heating to ensure that the carbon-increasing impregnation liquid will not flow out of the ceramic body after the impregnation is completed and during the second phenolic resin solution impregnation. As the main carburizing material, nano carbon black has nano-scale particle size, which can ensure smooth impregnation into silicon carbide ceramic body, increase the carbon content in the ceramic body, and react to generate more silicon carbide in the subsequent liquid silicon infiltration treatment. β-SiC ultrafine powder is dispersed into nano carbon black as an inert raw material. Combined with the use of dispersant, it can solve the problems of uneven dispersion, agglomeration and easy clogging of impregnation channels of nano carbon black. The addition of β-SiC ultrafine powder also prevents too much nano carbon black in the ceramic body, avoiding excessive volume expansion after reaction with silicon and generating internal stress. In addition, the thermal conductivity of β-SiC is better than that of α-SiC, which can improve the thermal conductivity of silicon carbide ceramics.
[0035] The silicon carbide ceramic body may be vacuum impregnated in the carburizing impregnation solution for 30 to 180 minutes, and may be vacuum impregnated in the phenolic resin solution for 15 to 120 minutes.
[0036] The curing can be carried out in a vacuum oven, an electric blast drying oven or a hot air circulation oven, the temperature can be 120 to 180° C., preferably 170° C., and the insulation time can be 2 to 4 hours, preferably 3 hours.
[0037] In some embodiments, in step (4), the liquid silicon infiltration treatment can be carried out in a vacuum high-temperature furnace, and the mass ratio of the carbon-impregnated silicon carbide ceramic body to Si can be 1:1-2; the temperature can be 1550-1650°C, preferably 1600°C, and the holding time can be 30-90 min, preferably 60 min.
[0038] Through liquid silicon infiltration treatment, reactive liquid Si can be infiltrated into a green body with a certain porosity through capillary force at high temperature, react with C in the green body and generate SiC. It has the advantages of short sintering time, low sintering temperature, and net size forming.
[0039] In summary, the present invention uses two different particle sizes of silicon carbide powders, large particles of silicon carbide form the main heat conduction channel, and small particles of silicon carbide fill the gaps between large particles of silicon carbide, so that the silicon carbides are connected to each other, ensuring the connectivity of the heat conduction channel, thereby improving the thermal conductivity of silicon carbide ceramics. In addition, the present invention uses two methods to improve the density of silicon carbide ceramics and reduce the content of residual silicon: (1) by grading the particle size of silicon carbide powder, increasing the bulk density of the powder, and increasing the silicon carbide content in the blank; (2) by preparing a vacuum impregnation liquid with a high carbon content, and then using a phenolic resin solution for secondary impregnation without debonding, the high carbon content impregnation liquid of the first impregnation can fill most of the relatively large pores, and the phenolic resin solution of the second impregnation can fill the remaining small pores. After debonding and cracking, a large amount of carbon is generated, which greatly improves the carbon density of the blank, thereby improving the density of silicon carbide after siliconization, reducing the content of residual silicon, and improving the thermal conductivity and elastic modulus of silicon carbide ceramics.
[0040] The high thermal conductivity and high modulus silicon carbide ceramics obtained by the preparation method provided by the present invention have a thermal conductivity greater than 220W / (m·K) and an elastic modulus greater than 350GPa; moreover, the steps are simple, the organic matter content is low, and the method has good engineering application prospects.
[0041] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.
[0042] Example 1
[0043] The method for preparing the high thermal conductivity and high modulus silicon carbide ceramic provided in this embodiment comprises the following steps: (1) Weigh 140 g of large-particle silicon carbide powder with a median particle size of 200 μm, 60 g of small-particle silicon carbide powder with a median particle size of 20 μm, 3 g of p-toluenesulfonic acid solvent and 33 g of silicon carbide grinding balls, place them on a horizontal ball mill for ball milling for 1 hour; then add 7 g of furan resin, place them on a horizontal ball mill for ball milling for 3 minutes, and obtain a silicon carbide raw material mixed slurry; (2) After the silicon carbide raw material mixed slurry is screened, it is quickly molded at a pressure of 30 MPa and a holding time of 2 minutes. After the pressing is completed, it is placed in an oven at 170° C. for curing for 3 hours, and then kept in a high-temperature vacuum furnace at 900° C. for 30 minutes to remove the organic binder to obtain a silicon carbide ceramic body; (3) Weighing 200 g of phenolic resin solution (the mass ratio of phenolic resin to anhydrous ethanol is 1:1), 20 g of SiC ultrafine powder with a particle size of 0.5 μm, 40 g of nano carbon black, 5 g of castor oil phosphate dispersant and 60 g of anhydrous ethanol, and stirring with a magnetic force for 24 h to prepare a carburizing impregnation solution; immersing the silicon carbide blank obtained in step (2) in the carburizing impregnation solution, and immersing it in a vacuum environment until no bubbles are generated, taking it out and wiping off the surface impregnation solution, and then keeping it in an oven at 170° C. for 3 h to complete curing; after the curing is completed, the silicon carbide blank is further immersed in the phenolic resin solution, vacuum impregnated again and cured at 170° C. for 3 h, and then kept in a high-temperature vacuum furnace at 900° C. for 30 min to remove the organic binder, thereby obtaining a carburized impregnated silicon carbide ceramic blank; (4) Placing silicon particles around the impregnated silicon carbide ceramic body, and performing liquid silicon infiltration treatment in a high-temperature vacuum furnace at 1600° C. for 60 minutes to obtain the silicon carbide ceramic with high thermal conductivity and high modulus.
[0044] Figure 1 This is a SEM image of the surface morphology of the high thermal conductivity and high modulus silicon carbide ceramic obtained in Example 1. As can be seen from the figure, the silicon carbide ceramic obtained in this example has very little residual silicon content and high density, wherein large-particle silicon carbide serves as the main ceramic skeleton, and small-particle silicon carbide and silicon carbide generated by reaction after impregnation are filled between large-particle silicon carbide. This free silicon is distributed in small amounts and independently, and the microstructure of continuous distribution of silicon carbide is conducive to the formation of heat conduction channels and improves the thermal conductivity of silicon carbide ceramics.
[0045] After testing, the density of the silicon carbide ceramics prepared in this embodiment is 3.09g / cm 3 , thermal conductivity is as high as 239.69W / (m·K), elastic modulus is 394GPa, and three-point bending strength is 256MPa.
[0046] Example 2
[0047] The method for preparing the high thermal conductivity and high modulus silicon carbide ceramic provided in this embodiment comprises the following steps: (1) Weigh 140 g of large-particle silicon carbide powder with a median particle size of 100 μm, 60 g of small-particle silicon carbide powder with a median particle size of 20 μm, 3 g of p-toluenesulfonic acid solvent and 33 g of silicon carbide grinding balls, place them on a horizontal ball mill for ball milling for 1 hour; then add 7 g of furan resin, place them on a horizontal ball mill for ball milling for 3 minutes, and obtain a silicon carbide raw material mixed slurry; (2) After the silicon carbide raw material mixed slurry is screened, it is quickly molded at a pressure of 30 MPa and a holding time of 2 minutes. After the pressing is completed, it is placed in an oven at 170° C. for curing for 3 hours, and then kept in a high-temperature vacuum furnace at 900° C. for 30 minutes to remove the organic binder to obtain a silicon carbide ceramic body; (3) Weighing 200 g of phenolic resin solution (the mass ratio of phenolic resin to anhydrous ethanol is 1:1), 20 g of SiC ultrafine powder with a particle size of 0.5 μm, 40 g of nano carbon black, 5 g of castor oil phosphate dispersant and 60 g of anhydrous ethanol, and stirring with a magnetic force for 24 h to prepare a carburizing impregnation solution; immersing the silicon carbide blank obtained in step (2) in the carburizing impregnation solution, and immersing it in a vacuum environment until no bubbles are generated, taking it out and wiping off the surface impregnation solution, and then keeping it in an oven at 170° C. for 3 h to complete curing; after the curing is completed, the silicon carbide blank is further immersed in the phenolic resin solution, vacuum impregnated again and cured at 170° C. for 3 h, and then kept in a high-temperature vacuum furnace at 900° C. for 30 min to remove the organic binder, thereby obtaining a carburized impregnated silicon carbide ceramic blank; (4) Placing silicon particles around the impregnated silicon carbide ceramic body, and performing liquid silicon infiltration treatment in a high-temperature vacuum furnace at 1600° C. for 60 minutes to obtain the silicon carbide ceramic with high thermal conductivity and high modulus.
[0048] After testing, the density of the silicon carbide ceramic is 3.05g / cm 3 , thermal conductivity is 227.16W / (m·K), elastic modulus is 367GPa, and three-point bending strength is 220MPa.
[0049] Example 3
[0050] The method for preparing the high thermal conductivity and high modulus silicon carbide ceramic provided in this embodiment comprises the following steps: (1) Weigh 140 g of large-particle silicon carbide powder with a median particle size of 200 μm, 60 g of small-particle silicon carbide powder with a median particle size of 100 μm, 3 g of p-toluenesulfonic acid solvent and 33 g of silicon carbide grinding balls, place them on a horizontal ball mill for ball milling for 1 hour; then add 7 g of furan resin, place them on a horizontal ball mill for ball milling for 3 minutes, and obtain a silicon carbide raw material mixed slurry; (2) After the silicon carbide raw material mixed slurry is screened, it is quickly molded at a pressure of 30 MPa and a holding time of 2 minutes. After the pressing is completed, it is placed in an oven at 170° C. for curing for 3 hours, and then kept in a high-temperature vacuum furnace at 900° C. for 30 minutes to remove the organic binder to obtain a silicon carbide ceramic body; (3) Weighing 200 g of phenolic resin solution (the mass ratio of phenolic resin to anhydrous ethanol is 1:1), 20 g of SiC ultrafine powder with a particle size of 0.5 μm, 40 g of nano carbon black, 5 g of castor oil phosphate dispersant and 60 g of anhydrous ethanol, and stirring with a magnetic force for 24 h to prepare a carburizing impregnation solution; immersing the silicon carbide blank obtained in step (2) in the carburizing impregnation solution, and immersing it in a vacuum environment until no bubbles are generated, taking it out and wiping off the surface impregnation solution, and then keeping it in an oven at 170° C. for 3 h to complete curing; after the curing is completed, the silicon carbide blank is further immersed in the phenolic resin solution, vacuum impregnated again and cured at 170° C. for 3 h, and then kept in a high-temperature vacuum furnace at 900° C. for 30 min to remove the organic binder, thereby obtaining a carburized impregnated silicon carbide ceramic blank; (4) Placing silicon particles around the impregnated silicon carbide ceramic body, and performing liquid silicon infiltration treatment in a high-temperature vacuum furnace at 1600° C. for 60 minutes to obtain the silicon carbide ceramic with high thermal conductivity and high modulus.
[0051] After testing, the density of the silicon carbide ceramic is 3.01g / cm 3 , thermal conductivity is 220.29W / (m·K), elastic modulus is 352GPa, and three-point bending strength is 184MPa.
[0052] Comparative Example 1
[0053] The preparation method of the silicon carbide ceramic provided in this comparative example refers to that of Example 1, with the main difference being that the vacuum impregnation with the carburizing impregnation liquid and the secondary impregnation with the phenolic resin solution process in step (3) are not performed.
[0054] Figure 2 The surface morphology SEM image of the silicon carbide ceramic prepared in Comparative Example 1. It can be seen from the figure that although the grading design results in a better particle stacking condition, the content of residual silicon is higher than that in Example 1 due to the lack of impregnation treatment.
[0055] After testing, the density of the silicon carbide ceramic is 2.94g / cm 3 , thermal conductivity is 173.58W / (m·K), elastic modulus is 317GPa, and three-point bending strength is 211MPa.
[0056] Comparative Example 2
[0057] The preparation method of the silicon carbide ceramic provided in this comparative example refers to that in Example 1, the main difference is that the vacuum impregnation carbon-enhancing impregnation liquid process in step (3) is not performed.
[0058] After testing, the density of the silicon carbide ceramic is 3.02g / cm 3 , thermal conductivity is 198.18W / (m·K), elastic modulus is 335GPa, and three-point bending strength is 238MPa.
[0059] Figure 3 The surface morphology structure SEM image of the silicon carbide ceramic prepared in Comparative Example 2. As can be seen from the figure, unlike Example 1, this comparative example is not impregnated with a carburizing impregnation liquid, but directly impregnated with a phenolic resin solution, resulting in an increase in the residual silicon content. Tests show that its density, thermal conductivity, elastic modulus and flexural strength all have a certain decrease, indicating that by first impregnating the carburizing impregnation liquid, using nano carbon black and ultrafine SiC powder to fill part of the pores of the blank, and then impregnating the phenolic resin solution to fill the remaining pores after curing, it is beneficial to improve the density of the silicon carbide ceramic, thereby improving the thermal conductivity, elastic modulus and flexural strength and other properties.
[0060] Comparative Example 3
[0061] The preparation method of the silicon carbide ceramic provided in this comparative example refers to that in Example 1, the main difference is that the secondary impregnation with the phenolic resin solution process in step (3) is not performed.
[0062] After testing, the density of the silicon carbide ceramic is 3.01g / cm 3 , thermal conductivity is 182.31W / (m·K), elastic modulus is 324GPa, and three-point bending strength is 225MPa. This is because the comparative example did not undergo secondary impregnation with phenolic resin solution, and there are still a small amount of pores between the silicon carbide powders, resulting in a decrease in the density, thermal conductivity, elastic modulus, and bending strength of the final silicon carbide ceramic.
[0063] Comparative Example 4
[0064] The preparation method of silicon carbide ceramics provided in this comparative example refers to that in Example 1, the main difference is that the carbon-enhancing impregnation liquid in step (3) does not contain SiC ultrafine powder and castor oil phosphate dispersant.
[0065] After testing, the density of the silicon carbide ceramic is 2.98g / cm 3 , thermal conductivity is 175.22W / (m·K), elastic modulus is 320GPa, and three-point bending strength is 217MPa. This is because the carbon-enhanced impregnation liquid in this comparative example only adds nano-carbon black, which is difficult to disperse and easily agglomerates, blocking the impregnation channel, and the impregnation liquid is difficult to fill the internal pores, which leads to a decrease in the performance of silicon carbide ceramics.
[0066] Comparative Example 5
[0067] The preparation method of the silicon carbide ceramic provided in this comparative example refers to that in Example 1, the main difference is that in step (1), no toluenesulfonic acid solvent is added.
[0068] After testing, it was found that due to the lack of solvent, the silicon carbide powder obtained in this comparative example could be barely molded, but the strength of the green billet after debonding was extremely low, and the subsequent impregnation and siliconization steps could not be carried out; although the strength of the green billet could be improved by further increasing the content of the binder, the organic matter content would increase.
[0069] Comparative Example 6
[0070] The preparation method of the silicon carbide ceramic provided in this comparative example refers to that in Example 1, the main difference is that in step (1), no furan resin binder is added.
[0071] After testing, it was found that due to the lack of a binder, the silicon carbide powder obtained in this comparative example had no adhesiveness and was difficult to be molded. The green billet had extremely low strength and could not be used for subsequent impregnation and siliconization steps.
[0072] Comparative Example 7
[0073] In this comparative example, commercially available silicon carbide powder was sintered at normal pressure, and silicon carbide ceramics were obtained after being kept at 2150° C. for 1 hour under normal pressure.
[0074] After testing, the density of the silicon carbide ceramic is 3.10g / cm 3 , thermal conductivity is 120W / (m·K), elastic modulus is 370GPa, and three-point bending strength is 390MPa. Since the sintering activity of silicon carbide is very low, the powder of silicon carbide sintered at normal pressure is very fine, usually nanometer or submicron level, resulting in very small grains of silicon carbide ceramics, and its thermal conductivity is much lower than that of the silicon carbide ceramics obtained in the embodiment of the present invention.
[0075] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing high thermal conductivity and high modulus silicon carbide ceramics, characterized in that: The preparation method comprises the following steps: (1) mixing silicon carbide raw material powder and a solvent for a first time, then adding a binder thereto and mixing for a second time to obtain a silicon carbide raw material mixed slurry; (2) forming the silicon carbide raw material mixed slurry into a green body and performing a heating and curing treatment, and then debonding to obtain a silicon carbide ceramic body; (3) performing a carbon-enhanced impregnation treatment on the silicon carbide ceramic body and performing a debonding treatment to obtain a carbon-enhanced impregnated silicon carbide ceramic body; (4) The carbon-impregnated silicon carbide ceramic body is subjected to liquid silicon infiltration treatment to obtain the high thermal conductivity and high modulus silicon carbide ceramic.
2. The preparation method according to claim 1, characterized in that: In step (1), the silicon carbide raw material powder includes 2 to 4 silicon carbide raw material powders of different particle size ranges; preferably, the silicon carbide raw material powder includes silicon carbide raw material powders of two particle size ranges, namely, large-particle-size silicon carbide raw material powder and small-particle-size silicon carbide raw material powder; More preferably, the median particle size of the large-particle silicon carbide raw material powder is 100-500 μm, the median particle size of the small-particle silicon carbide raw material powder is 1-100 μm, and the mass ratio of the large-particle silicon carbide raw material powder to the small-particle silicon carbide raw material powder is 6-8:2-4.
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the solvent includes at least one of dilute sulfuric acid, hydrochloric acid, phosphoric acid, boric acid, oxalic acid, maleic anhydride, citric acid, malic acid, polyaluminum phosphate, benzenesulfonic acid or phenolsulfonic acid, preferably benzenesulfonic acid or phenolsulfonic acid, more preferably p-toluenesulfonic acid.
4. The preparation method according to any one of claims 1 to 3, characterized in that In step (1), the binder includes at least one of polyvinyl alcohol, polyvinyl butyral, polymethyl methacrylate, polyvinyl pyrrolidone, water glass, silica sol, epoxy resin, furan resin, and phenolic resin.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (1), taking the total mass of the silicon carbide raw material powder, solvent and binder as 100%, the mass of the silicon carbide raw material powder accounts for 85-97wt%, the mass of the solvent accounts for 1-5wt%, and the mass of the binder accounts for 2-10wt%.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (2), the temperature of the heating and curing treatment is 120-180° C., preferably 170° C.; the insulation time is 2-4 hours, preferably 3 hours.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In step (3), the process of the carbon enrichment impregnation treatment includes: vacuum impregnating the silicon carbide ceramic body in a carbon enrichment impregnation solution, then curing it, and then continuing to vacuum impregnate it in a phenolic resin solution and curing it again.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The raw material composition of the carbon-increasing impregnation liquid includes: 50-80wt% phenolic resin solution, 5-30wt% SiC ultrafine powder, 5-30wt% nano carbon black, and 1-5wt% dispersant; Preferably, the phenolic resin solution is a mixed solution of phenolic resin and anhydrous ethanol, the content of anhydrous ethanol is 30-70wt%, the SiC ultrafine powder is β-SiC ultrafine powder with a particle size of 50-800nm, the particle size of nano carbon black is 1-100nm, and the dispersant is castor oil phosphate or castor oil.
9. The preparation method according to any one of claims 1 to 8, characterized in that: In step (4), the temperature of the liquid silicon infiltration treatment is 1550-1650° C., preferably 1600° C., and the insulation time is 30-90 min, preferably 60 min.
10. A high thermal conductivity, high modulus silicon carbide ceramic obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The high thermal conductivity and high modulus silicon carbide ceramic has a thermal conductivity greater than 220 W / (m·K) and an elastic modulus greater than 350 GPa.
Citation Information
Cited By
High-density silicon carbide ceramic semiconductor material and preparation method thereof
CN122212767A